The Effect of Education Breastfeeding to Breastfeeding Self Efficacy in Central Java Indonesia - Aris Prastyoningsih; Dheny Rohmantika; Erinda Nur Pratiwi; Ajeng Maharani; Amrina Nur Rohmah (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2021)
The low coverage of exclusive breastfeeding is influenced by several internal factors. Breastfeeding Self-efficacy can be increased through knowledge, skills about breastfeeding. Efforts to build knowledge and skills of mothers in breastfeeding can be done through breastfeeding education. This study aims to determine the effect of providing breastfeeding education with booklets on the breasfeeding self-efficacy in post partum mothers in Klaten, Central Java, Indonesia. This research is quantitative research with one group pre test - post test design. This research was conducted at 2 independent midwifery in Klaten on July to September 2020. Sampling technique used was purposive sampling with inclusion criteria. Statistical analysis used Univariate analysis and Bivariate analysis using paired t-test. There was a significant increase in the mean breastfeeding self-efficacy before and after breastfeeding education with booklets with a significant of 0.000 (> 0.000 at α = 0.05 and a confidence level of 95%. There is the effect of breastfeeding education with a booklet on self efficacy of breastfeeding on postpartum mother. Education breasfeeding can be used by midwives or health promotion to educate pregnant women and post-partum mothers to increase self efficasy to support the successfull of exclusive breastfeeding.